A ratiometric fluorescent probe for the detection of formaldehyde in aqueous solution and air via Aza-Cope reaction. (December 2019) - Zhai, Beibei; Zhang, Yaoqing; Hu, Ziwei; He, Jiaopu; Liu, Jia; Gao, Chao; Li, Wei
Abstract: Herein, we explored a novel ratiometric fluorescent probeTP-FA, which could detect FA not only in aqueous solution, but also in air by loading on the fabric and cotton. The test cotton displayed the much faster response to FA than the test fabric and test solution. When the test cotton was exposed to FA vapor, the Aza-Cope reaction ofTP-FA with FA changed the emission color from blue to green within 45 min by the combined aggregation-induced emission (AIE) and intramolecular charge transfer (ICT) effects. Moreover, the test cotton exhibited the high selectivity to gaseous FA, and it could point out the concentration of FA vapor according to the emission color. Graphical abstract: The ratiometric fluorescent probeTP-FA could detect formaldehyde (FA) not only in aqueous solution, but also in air by loading on the fabric and cotton.Image 1 Highlights: A novel ratiometric fluorescent probeTP-FA for formaldehyde has been explored. ProbeTP-FA was able to detect formaldehyde in aqueous solution. The test fabric and test cotton loaded withTP-FA could detect formaldehyde gas. The test cotton showed the faster response to formaldehyde than other tools.